Chemo-photothermal immunotherapy for eradication of orthotopic tumors and inhibition of metastasis by intratumoral injection of polydopamine versatile hydrogels - Bo Zhuang; Ting Chen; Yueqi Huang; Zhimei Xiao; Yiguang Jin (Elsevier, 2022)
Cancer remains one of the leading causes of death globally and metastasis always leads to treatment failure. Here, we develop a versatile hydrogel loading photothermal agents, chemotherapeutics, and immune-adjuvants to eradicate orthotopic tumors and inhibit metastasis by combinational therapy. Hydrogel networks were synthesized via the thiol-Michael addition of polydopamine (PDA) with thiolated hyaluronic acid. PDA acted as a cross-linking agent and endowed the hydrogel with excellent photothermal property. Meanwhile, a chemotherapeutic agent, doxorubicin (DOX), was loaded in the hydrogel via π‒π stacking with PDA and an immune-adjuvant, CpG-ODN, was loaded via electrostatic interaction. The release of DOX from the hydrogel was initially slow but accelerated due to near infrared light irradiation. The hydrogels showed remarkably synergistic effect against 4T1 cancer cells and stimulated plenty of cytokines secreting from RAW264.7 cells. Moreover, the hydrogels eradicated orthotopic murine breast cancer xenografts and strongly inhibited metastasis after intratumoral injection and light irradiation. The high anticancer efficiency of this chemo-photothermal immunotherapy resulted from the strong synergistic effect of the versatile hydrogels, including the evoked host immune response. The combinational strategy of chemo-photothermal immunotherapy is promising for highly effective treatment of breast cancer.